The Road to Spindletop Economic Change in Texas, 1875-1901 - Spratt, John Stricklin (University of Texas Press, 2021)
This book is an economic history of Texas at the end of the nineteenth century. In 1875, Texas was an agrarian state with limited industry. A generation later, agriculture was heavily commercialized, thousands of miles of railroads carried people and goods around the state, and urban populations increased rapidly. Even before the Spindletop gusher that irrevocably changed the state's future, Texas had already moved far from its days as a Mexican and American frontier